Medical zero waste water central membrane processing method and water machine thereof - BAO ZHIGUO (2008)
The invention discloses a treatment method of medical reverse osmosis water and equipment thereof. The method is to have the pretreatment of raw water, filter water in a secondary filter, lift water pressure by a high head pump and finally filter and concentrate water in a reverse osmosis membrane. The low conductivity water filtered and concentrated in the reverse osmosis membrane is gathered in a pure water tank and to be used after treatment while the waste water from the reverse osmosis membrane is put into a set of or more degermation velum or low desalination velum. The water is gathered in one or more pure water tank(s) after filtration and to be used after treatment. The device consists of a pretreatment system, a central membrane processing system and a final processing system, wherein, the central membrane processing system comprises the secondary filter, the high head pump and the reverse osmosis membrane which are connected by pipes. A waste water outlet of the reverse osmosis membrance is connect